Investigation of parameters affecting the high harmonic generation from monolayer WS2. Issue 7 (27th December 2022) - Sadeghifaraz, Amin; Irani, Elnaz; Monfared, Mohammad
Abstract: The effect of crystal symmetry in the high harmonic generation of monolayer WS2 is investigated using the three‐dimensional time‐dependent density functional theory. The role of linearly and elliptically polarized laser, as well as the crystall orientation in the enhancement of harmonics yield, is explored. Also, the wavelength dependence of the harmonic yield and the intensity dependence of cutoff harmonic order are studied. The former shows an exponential decay with increasing the driving laser wavelength, and the latter reveals a linear dependency of cutoff harmonic to the driving laser field. Moreover, a dual pulse system as a driving laser, a fundamental 1.3 μm laser pulse synthesized by its second harmonic, is proposed which could increase the cutoff harmonic order up to 24th (22 eV). Our results pave the way for controlling and enhancing high harmonic spectra from solids. Abstract : Wavelength scaling of the harmonic yield for monolayer WS2 driven by lasers with different central wavelengths. All driving lasers are assumed to have a peak intensity of 1 TW/cm 2, a constant pulse duration of 5 fs, and a linear polarization along the zigzag axis. The harmonic yield is integrated in the range of 4–8 eV.